Identification of miRSNPs associated with the risk of multiple myeloma. Issue 3 (9th November 2016) - Macauda, Angelica; Calvetti, Diego; Maccari, Giuseppe; Hemminki, Kari; Försti, Asta; Goldschmidt, Hartmut; Weinhold, Niels; Houlston, Richard; Andersen, Vibeke; Vogel, Ulla; Buda, Gabriele; Varkonyi, Judit; et al.
Abstract : Multiple myeloma (MM) is a malignancy of plasma cells usually infiltrating the bone marrow, associated with the production of a monoclonal immunoglobulin (M protein) which can be detected in the blood and/or urine. Multiple lines of evidence suggest that genetic factors are involved in MM pathogenesis, and several studies have identified single nucleotide polymorphisms (SNPs) associated with the susceptibility to the disease. SNPs within miRNA‐binding sites in target genes (miRSNPs) may alter the strength of miRNA–mRNA interactions, thus deregulating protein expression. MiRSNPs are known to be associated with risk of various types of cancer, but they have never been investigated in MM. We performed an in silico genome‐wide search for miRSNPs predicted to alter binding of miRNAs to their target sequences. We selected 12 miRSNPs and tested their association with MM risk. Our study population consisted of 1, 832 controls and 2, 894 MM cases recruited from seven European countries and Israel in the context of the IMMEnSE (International Multiple Myeloma rESEarch) consortium. In this population two SNPs showed an association with p < 0.05: rs286595 (located in gene MRLP22 ) and rs14191881 (located in gene TCF19 ). Results from IMMEnSE were meta‐analyzed with data from a previously published genome‐wide association study (GWAS). The SNPs rs13409 (located in the 3′UTR of the POU5F1 gene), rs1419881 ( TCF19 ), rs1049633, rs1049623 (both in DDR1 ) showed significant associations with MM risk. In conclusion, we sought to identify genetic polymorphisms associated with MM risk starting from genome‐wide prediction of miRSNPs. For some mirSNPs, we have shown promising associations with MM risk. Abstract : What's new? Even though deregulation of miRNA expression has been associated with human cancers little information is available regarding their relation with MM susceptibility. We performed an in silico genome‐wide search for miRSNPs and selected the most promising ones for an association study. The SNPs with the strongest associations with MM risk are localized in genes which have never been related with MM.